Malignant tumors of the small intestine: A case series - Sharon Slomovich; Mahnoor Khan; Neal Shah; Frank G Gress (Archives of Clinical Gastroenterology - Peertechz Publications, 2023)
Small bowel malignancies are rare, yet their incidence has been rising in the last decade. The main histological types are adenocarcinomas, neuroendocrine and stromal tumors, sarcomas, and lymphomas. The clinical presentation is often nonspecific, making it a challenging diagnosis that results in delayed treatment. We report a case series of four patients who present with non-specific gastrointestinal symptoms and a subsequent diagnosis of a small bowel malignancy. While advanced endoscopic techniques have improved our ability to identify these uncommon tumors, in our case series, the definitive diagnosis was delayed due to the ambiguous presentation. Larger studies are warranted for better diagnosis and treatment of small bowel malignancies.